(untitled) (Bangladesh Journal of Anatomy, 2011)
Objective: To explore present status of clinical teaching in Bachelor of Dental Surgery course of Bangladesh. Methods: This study was conducted from July 2007 to June 2008 upon conveniently selected teachers (n=49) of clinical departments and students of 3rd year (n=83) and 4th year (n=111) of two government and two private dental institutes of Bachelor of Dental Surgery course. Data were collected using one semistructured self-administered questionnaires. Result: It was found that most of the clinical classes are conducted by lecturers, assistant professors. These classes were held mostly in morning which extended occasionally up to afternoon. Majority of teachers followed the curriculum to conduct clinical classes. They agreed that the students are benefited through these clinical classes and they learn how to examine a patient and take patients’ history and other clinical skills. They informed that inadequate number of teachers and patients are important barriers for clinical teaching. They suggested that clinical classes should be taken by the senior teachers and sufficient materials and instruments should be available for this purpose. It was also proposed that sufficient number of patients and increased number of teachers should be ensured. Discussion and recommendations: The barriers should be minimized and necessary actions should be taken as per suggestions given the teachers and students. Key words: Clinical teaching learning; Bedside teaching learning; Bachelor of Dental Surgery Course Bangladesh. DOI: 10.3329/bja.v8i2.7021 Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 76-80